Implant Restorations: A Step-by-Step Guide - Drago, Carl (Wiley, 2019)
The fourth edition of Implant Restorations: A Step-by-Step Guide provides a wealth of updated and expanded coverage on detailed procedures for restoring dental implants. Focusing on the most common treatment scenarios, it offers concise literature reviews for each chapter and easy-to-follow descriptions of the techniques, along with high-quality clinical photographs demonstrating each step. Comprehensive throughout, this practical guide begins with introductory information on incorporating implant restorative dentistry in clinical practice. It covers diagnosis and treatment planning and digital dentistry, and addresses advances in cone beam computerized tomography (CBCT), treatment planning software, computer generated surgical guides, rapid prototype printing and impression-less implant restorative treatments, intra-oral scanning, laser sintering, and printing/milling polymer materials. Record-keeping, patient compliance, hygiene regimes, and follow-up are also covered. * Provides an accessible step-by-step guide to commonly encountered treatment scenarios, describing procedures and techniques in an easy-to-follow, highly illustrated format * Offers new chapters on diagnosis and treatment planning and digital dentistry * Covers advances in cone beam computerized tomography (CBCT), computer generated surgical guides, intra-oral scanning, laser sintering, and more An excellent and accessible guide on a burgeoning subject in modern dental practice by one of its most experienced clinicians, Implant Restorations: A Step-by-Step Guide, Fourth Edition will appeal to prosthodontists, general dentists, implant surgeons, dental students, dental assistants, hygienists, and dental laboratory technicians.